Descrição da fauna parasitária de raias e tubarões marinhos (Elasmobranchii), fauna acompanhante da pesca comercial no litoral Sul e Sudeste do Brasil - Napoleão, Silvia Roselli [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The main objective of this study was to determine the diversity of parasites in marine sharks and rays in the south and southeast coast of Brazil, catches by pair trawls and by bottom trawling of small and medium size– for fishery of shrimp Xiphopenaeus kroyeri and Penaeus brasiliensis, respectively, and landed in the cities of Santos and Guaruja - SP . Between april 2012 and april 2013, fourteen species of stingrays and three species of sharks, totaling 129 animals, were necropsied: 7 sharks and 116 rays. As a result, refers reoccurrence of nematode Proleptus acutus in Atlantoraja platana , Rhinobatos percellens, Rhinobatos horkelli, Zapteryx brevirotris, Rioraja agassizii and Atlatoraja cyclophora, recurrence of Procamallanus (Spirocamallanus) pereirae in Atlantoraja castenaui and Atlatoraja cyclophora, and recurrence the Cestoda Rhinoptericola megacantha in Rhinoptera brasiliensis . It refers also occurrence of six different species of cestodes, not yet recorded: two of the species found (Cestoda sp. gen. 1 and Cestoda gen. sp. 2) belong to genera not yet described in the literature . The other cestodes were identified only at genus level (Rhodobothrium sp., Cairaeanthum sp., Uncibilocularis sp. and Tiarabothrium sp.), because it does not characterize the species already described them

O objetivo principal deste estudo foi determinar a diversidade dos parasitos que ocorrem nas raias e tubarões marinhos no litoral sul e sudeste do Brasil, capturados pela pesca de arrasto-de-parelha e de arrasto de fundo duplo de pequeno e médio porte - pesca do camarão sete-barbas (Xiphopenaeus kroyeri) e pesca do camarão-rosa (Penaeus brasiliensis) respectivamente, e desembarcados nas cidades de Santos e Guarujá-SP. Entre abril de 2012 e abril de 2013, foram necropsiadas quatorze espécies de raias e três espécies de tubarões, totalizando 123 exemplares: 7 tubarões e 116 raias. Como resultados, reporta-se nova ocorrência do nematoda Proleptus acutus em Atlantoraja platana, Rhinobatos percellens, Rhinobatos horkelli, Zapteryx brevirotris, Rioraja agassizii e Atlatoraja cyclophora, e nova ocorrência de Procamallanus (Spirocamallanus) pereirae em Atlantoraja castenaui e Atlatoraja cyclophora, e nova ocorrência do cestoda Rhinoptericola megacantha em Rhinoptera brasiliensis. Reporta-se também ocorrência de seis diferentes espécies de cestóides, ainda não registrados: duas das espécies encontradas (Cestoda gen. sp. 1 e Cestoda gen. sp. 2) pertencem a gêneros ainda não descritos em literatura. Os demais cestoides foram identificados apenas em nível de gênero (Rhodobothrium sp., Cairaeanthum sp., Tiarabothrium sp e Uncibilocularis sp.), pois não se caracterizam nas espécies já descritas dos mesmos
Keywords: Cestoide; Nematoda; Raia (Peixe); Tubarão; Parasito; Marine biology